Social Media Potentials in Supporting Women Entrepreneurship: The Case of Egypt - Aboutaleb, Gehan Ahmed (AUC Knowledge Fountain, 2020)
The number of women entrepreneurs in Egypt starting and running their business online has been remarkably rising in recent years. Thanks to social media’s ability to harness some of the obstacles women business-owned enterprises encounter, it has become an essential platform for providing women with entrepreneurial opportunities and facilitating their own business. Social media is becoming more of an indispensable instrument for the businesses' survival, especially in light of the implications posed by the recent outbreak of global pandemic COVID-19 in terms of movement restrictions and social distancing measures. However, a dearth in the literature on the impact of social media on entrepreneurship still exists, especially from a gender perspective. The aim of this study is, as such, to explore the extent to which these means could support creating entrepreneurial opportunities for women entrepreneurs in Egypt. The study used a quantitative approach by analyzing data collected from a sample of 96 women entrepreneurs operating online through conducting Exploratory Factor Analysis (EFA), reliability, and regression tests. This research's main findings illustrate that social media proved to be an instrumental tool for creating an enabling environment for women entrepreneurs, whereby they can run their business while achieving their work-family life balance. It was also recognized as an affordable and technically accessible medium to develop, improve, and promote women's business services and products. Keywords: women entrepreneurs, entrepreneurship, social media, self-efficacy, social capital, empowerment, digital financial solutions, technology, marketing, social capital, networking.